Chemoselective Bromination of Dienoates. Issue 34 (7th August 2020) - Kobelevskaya, Valentina A.; Popov, Alexander V.; Zinchenko, Sergey V.; Rulev, Alexander Yu.
Abstract : A variety of tetra‐, di‐ and monobromo derivatives of dienoates were prepared from parent polyunsaturated esters under mild conditions. According to proposed protocol the target bromoesters were easily obtained as a rule in good yields and high selectivity. Abstract : One isomer or another! Chemo‐ and stereoselectivity of dienoates bromination depends strongly on the substituent nature in starting ester and reaction conditions.